Single-atom bridges across biotic-abiotic interfaces facilitate direct electron transfer for solar-to-chemical conversion - Wentao Song; Yong Liu; Yao Wu; Cheng Wang; Zhourui Liu; Yinan Liu; Xinyue Zhang; Lei Cao; Bowen Li; Bo Song; Bin Cao; Yingfang Yao; et al. (Nature Communications)
Abstract Biotic-abiotic hybrid systems show significant promise for solar-to-chemical conversion by integrating intracellular biocatalytic pathways with artificially synthesized semiconductors. However, due to intricate interfacial connection and ubiquitous heterogeneities between microorganisms and materials, it remains challenging to achieve atomically precise interface contact and elucidate electron transport mechanism at the single-/sub-cell levels for efficient solar energy transformation. Herein, we report a general design of facilitating direct electron transfer pathway through constructing single-atom bridges across biotic-abiotic interfaces to enhance solar-to-chemical conversion. Specifically, using C3N4/Ru-Shewanella hybrid system as a demonstration, we discover that single-atom bridges promote effective charge separation and reduce electron transfer barriers at the biohybrid interfaces. Moreover, operando single-cell photocurrent technique and theoretical calculations further quantitatively unravel that C3N4/Ru-Shewanella with a unique Ru-N4 interfacial structure exhibits a 11.0-fold increase in direct electron uptake compared to C3N4-Shewanella. In contrast to Shewanella and C3N4-Shewanella, C3N4/Ru-Shewanella shows 47.5- and 14.2-fold improvement for solar-driven H2 production, respectively, achieving a remarkable quantum yield of 8.46%. This work, further supported via proteomic analysis and C3N4/Cu-Shewanella biohybrids, highlights the universal strategy of single atoms mediating direct electron uptake and provides insights into atomic-level charge dynamics in microbe-semiconductor biohybrids towards solar energy utilization.